2018
DOI: 10.1152/ajpendo.00050.2018
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of CTRP3 prevents alcohol-induced hepatic triglyceride accumulation

Abstract: This study tested the ability of a novel adipose tissue derived cytokine, C1q TNF Related Protein 3 (CTRP3), to prevent alcohol-induced hepatic lipid accumulation, or alcoholic fatty liver disease (ALD). Previous work has demonstrated that CTRP3 is effective at preventing high fat diet-induced fatty liver, however, the potential of CTRP3 to inhibit ALD has not been explored. To test the potential protective effects of CTRP3, transgenic mice overexpressing CTRP3 (Tg) or wildtype littermates (WT) were subjected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 45 publications
(61 reference statements)
2
19
0
Order By: Relevance
“…Thus, there has been renewed interest in developing effective therapeutic strategies to prevent alcoholic fatty liver disease [ 4 , 6 , 9 , 13 , 65 , 66 ]. Our data, combined with the finding that CTRP3 prevents alcohol-induced fatty liver disease [ 55 ], identifies CTRP3 as an ideal candidate to develop novel treatments for alcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Thus, there has been renewed interest in developing effective therapeutic strategies to prevent alcoholic fatty liver disease [ 4 , 6 , 9 , 13 , 65 , 66 ]. Our data, combined with the finding that CTRP3 prevents alcohol-induced fatty liver disease [ 55 ], identifies CTRP3 as an ideal candidate to develop novel treatments for alcoholic fatty liver disease.…”
Section: Discussionmentioning
confidence: 73%
“…As CTRP3 levels are selectively reduced in ethanol fed female mice, this provides a novel mechanism to explore the increased susceptibility of females to alcoholic cirrhosis. Our previous work has shown that CTRP3 acts directly on liver tissue to stimulate lipid oxidation and attenuate both diet-induced and alcoholic fatty liver disease [ 38 , 55 ]. In support of this, CTRP3 levels are found to be lower in human patients with diet-induced hepatic steatosis, or non-alcoholic fatty liver disease [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic overexpression of CTRP3 has been shown to prevent both alcoholic and nonalcoholic fatty liver disease in rodent studies (Peterson et al, ; Trogen et al, ). CTRP3 also reduces hepatic triglyceride synthesis and secretion, further supporting the role of CTRP3 in triglyceride regulation (Peterson et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The primary hypothesis was that, although total levels of circulating CTRP3 will be similar between people with type 2 diabetes compared with nondiabetic controls, there will be a difference between groups in the circulating oligomeric state of CTRP3. The secondary purpose of this study was to determine whether the circulating oligomeric state of CTRP3 correlates with the circulating levels of inflammatory cytokines or triglycerides as CTRP3 has been previously demonstrated to attenuate inflammation and to reduce triglyceride levels (Hofmann et al, ; Kopp, Bala, Buechler, et al, ; Kopp, Bala, Weigert, et al, ; Li et al, ; Petersen et al, ; Peterson et al, , ; Schmid, Kopp, Hanses, Karrasch, & Schaffler, ; Tan et al, ; Trogen et al, ; Yang et al, ; Yoo et al, ).…”
Section: Introductionmentioning
confidence: 99%